ANGGREK TANAH DI KAWASAN TAMAN WISATA ALAM SICIKE-CIKE SUMATERA UTARA DAN UPAYA KONSERVASINYA DI KEBUN RAYA SAMOSIR - Sri Hartini (Universitas Pakuan, 2017)
Terestrial orchid research has been conducted in the area of Sicike-cike Nature Park, North Sumatra. The research was conducted in with exploration method. No less than 12 types of terestrial orchids are found in this region, namely Spathoglottis plicata Blume, Spathoglottis aurea Lindl., Phaius callosus (Blume) Lindl., Calanthe triplicata Ames, Calanthe pulchra (Blume) Lindl., Calanthe chrysoglossoides J.J. Sm., Calanthe aurantiaca Ridl., Cymbidium ensifolium (L.) Sw., Arundina graminifolia (D.Don) Hochr., Neuwiedia zollingeri Rchb.f. var. zollingeri Rchb.f., Paphiopedilum tonsum (Rchb.f.) Stein, and Liparis sp. All types of orchids are then grown in the nursery of Samosir Botanical Gardens for ex-situnya conservation efforts. Two months after planting almost all species grow well, even some of them have produced flowers. Orchids A. graminifolia, S. aurea and S. plicata are the best-growing species.Â Key words : Terestrial orchid,Â Sicike-cike Nature Park, conservation, Samosir Botanical Garden